Esophageal lung associated to isolated dextrocardia in a six-month-old infant - Malak Boughdir; Aida Daib; Habib Bouthour; Sameh Tlili; Syrine Laribi; Rym Kchaou; Rabiaa Ben abdallah; Youssef Hellal; Nejib Kaabar (Elsevier, 2022)
Congenital bronchopulmonary foregut malformation (CBPFM) is a rare congenital malformation involving both the digestive and the respiratory system. Esophageal lung is an entity belonging to this group. Few cases have been reported. Diagnostic can be a challenge in some case. Much closer cooperation between pediatric surgeons and radiologists is essential to all investigations of these congenital malformations in particular to those associated to other congeniatl abnormality.Herein we describe the diagnostic and therapeutic approach in a six months old girl with esophageal lung.associated to dextrocardia.